Program Desa Binaan STAIN Teungku Dirundeng Meulaboh di Gampong Pasi Mesjid Kecamatan Meureubo Kabupaten Aceh Barat - Sumardi Efendi; Syaibatul Hamdi; Fedry Saputra; Muhammad Iqbal; Hendra SH; Aini Safitri; Danil Zulhendra; Dar Kasih; Ramli (Yayasan Sumber Daya Manusia Cerdas, 2023)
Foster Village is a community development program that aims to improve the quality of life in rural areas. This program focuses on various aspects of community development, such as education, the economy, and community empowerment. This program was implemented by STAIN Teungku Dirundeng Meulaboh in Gampong Pasi Mesjid, Meureubo District, West Aceh Regency from October 28 to November 28, 2022. Activities in this study used the Participatory Action Research (PAR) mentoring method, from the research results it was concluded that the Assisted Village program by The campus aims to develop the village so that it becomes an independent village and improves the welfare of the village community. This program also provides learning opportunities and contributions for program participants and involves campuses, lecturers, and students in village development efforts.